2012
DOI: 10.1183/09031936.00145009
|View full text |Cite
|
Sign up to set email alerts
|

PPAR ligands decrease human airway smooth muscle cell migration and extracellular matrix synthesis

Abstract: Airway smooth muscle cells produce extracellular matrix proteins, which in turn can promote smooth muscle survival, proliferation and migration. Currently available therapies have little effect on airway smooth muscle matrix production and migration. Peroxisome proliferatoractivated receptor (PPAR) ligands are reported to decrease migration and matrix production in various cell lines. In this study, we examined the effect of PPAR ligands on human airway smooth muscle (HASM) matrix production and migration.PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Cultures of human airway smooth muscle cells (HASMC) were generated from airways obtained from lung cancer patients (ex–smokers, five diagnosed with COPD and 2 with no other conditions) undergoing thoracic surgery at St Joseph’s Healthcare Hamilton after obtaining their informed consent and with the approval of the local Research Ethics Board (approval RP#00-1839). Smooth muscle cells were isolated from disease-free areas of the airways and expanded in RPMI supplemented with 10% fetal bovine serum (FBS) and 1% L-Glutamine for up to 8 passages as previously described [ 45 ]. For analysis of cytokine synthesis, HASMC were plated at a cell density of 10,000- 20,000 cells per well in 24-well or 96-well tissue culture plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Cultures of human airway smooth muscle cells (HASMC) were generated from airways obtained from lung cancer patients (ex–smokers, five diagnosed with COPD and 2 with no other conditions) undergoing thoracic surgery at St Joseph’s Healthcare Hamilton after obtaining their informed consent and with the approval of the local Research Ethics Board (approval RP#00-1839). Smooth muscle cells were isolated from disease-free areas of the airways and expanded in RPMI supplemented with 10% fetal bovine serum (FBS) and 1% L-Glutamine for up to 8 passages as previously described [ 45 ]. For analysis of cytokine synthesis, HASMC were plated at a cell density of 10,000- 20,000 cells per well in 24-well or 96-well tissue culture plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, therapeutic agents such as corticosteroids and even ␤ 2 -agonists can reduce proliferation (19,86). Furthermore, peroxisome proliferatoractivated receptor (PPAR)-␥ ligands can blunt ASM proliferation, migration, and ECM formation (63,72,73,250,293), and this mechanism may be of interest, given its emerging role in lung development and injury (180,220,247,260). Finally, there is increasing interest in atypical anti-inflammatory stimuli such as vitamin D (44,50).…”
Section: L921mentioning
confidence: 99%
“…The precise mechanism of how LXR inhibits ASMC migration has yet to be established, but it has been speculated that it is not the Src Kinase, Akt or P38 MAPK pathways [ 107 ]. With respect to PPAR receptors, Stephen et al, reported that activation of PPAR receptors expressed on human ASMCs, resulted in decreased migration towards PGDF, an effect independent both of the promotion of PTEN activity, and inhibition of Akt phosphorylation [ 110 ]. They determined that the PPAR-mediated inhibition of ASMC migration was through an increase in intracellular cAMP, partly mediated by the induction of COX-2 and production of PGE 2 [ 110 ].…”
Section: Therapeutic Targets and Inhibitors Of Airway Smooth Muscle Cmentioning
confidence: 99%